Attachment and Relationship Satisfaction: Mediating Role of Perception of the Partner's Investment. (2020) - Londero-Santos, Amanda; Natividade, Jean Carlos; Féres-Carneiro, Terezinha
Abstract: This study investigated the role of perception of the partner's investment (PPI) as a mediator of the relation between attachment and relationship satisfaction. The participants in the study were 1088 Brazilians who were involved in a committed monogamous romantic relationship. Relations between study variables were tested using structural equations. The results showed that PPI fully mediated the relation between attachment-related anxiety and avoidance and relationship satisfaction. Attachment factors that were mediated by PPI explained 80.7% of the variance of relationship satisfaction. The results revealed that higher levels of attachment-related avoidance and anxiety were associated with a lower PPI and consequently lower relationship satisfaction. Therapeutic interventions for couples may reduce perceptual bias, mainly when attachment levels of the dyad are known.